Lithuania’s Agriculture and Food Market and Globalization - Garuckas, Rimantas (Ekonomika, 2002)
Agriculture in Lithuania - traditional, important, multiple, part of Lithuania’s establishment. In the future of Lithuania will be not protected from competition in agriculture and food sector because of globalization process. So in respect of that, there must be given priorities for that production which is most suitable to provide in Lithuania’s agriculture and food sector. Today most important aim is to integrate Lithuania’s agriculture in EU market so that competition with them would be at the same level. Because only well supported (with latest technologies) Lithuania’s agriculture market is able to survive in EU market.Priorities must be given for these agriculture and food market sectors: production of milk, production of meat, razing animals, gardening, oil-bearing and unconventional plants, grain, sugarbeets. The problem is that these products are not protected from EU competition in the inside and outside markets because of low level of technology progress, big production expenses, lack of money.